Implementasi Honeypot Sebagai Pendeteksi Serangan Pada Virtual Private Server (VPS) - M. Alamsyah Pratama; Herri Setiawan; Zaid Romegar Mair (Jurnal Software Engineering and Computational Intelligence, 2023)
VPS (Virtual Private Server) is a server virtualization technology that is currently widely used by users for a variety of purposes, including personal, work, office, and business. Virtual Private Server (VPS) is a technology that uses VPS. Since renting a virtual private server (VPS) is less expensive than purchasing or renting a dedicated server, VPS is widely used. However, VPS has some disadvantages as well, one of which concerns security. The Intrusion Detection System (IDS), the Virtual Private Network (VPN), and the Honeypot are just a few of the other options that can be utilized to secure servers. The Honeypot application is needed to protect Virtual Private Server (VPS), which requires a detection application that can reduce attacks on VPS. Cowrie is able to detect and record all attacks that occur on the server based on the results of attack testing that was carried out 25 times for each attack test, beginning with port scanning and progressing through DDoS attacks, brute force attacks, and individual, double, and multiple tests. considered to be very effective, but when multiple attacks were carried out simultaneously, the server experienced a downtime or lag